2016
DOI: 10.1111/hsc.12376
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related stigma affects the quality of life of people living with diabetes mellitus in Switzerland: implications for healthcare providers

Abstract: What is known about this topic• Recent studies reported that persons living with diabetes (PWD) experience stigma (discrimination and stereotypes) due to their health condition.• Surveys suggest that PWD affected by discrimination report lower scores of well-being, experience higher levels of distress and score lower in quality of life. What this paper adds• This study establishes experienced and perceived stigma of PWD living in Switzerland and thus, provides an insight into the situations in which PWD feel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
82
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 31 publications
14
82
0
3
Order By: Relevance
“…In a study of people living with diabetes (n 5 3,347), data from a self-administered questionnaire demonstrated that perceived stigma is associated with increased psychological distress, depressive symptoms, decreased social support, and decreased quality of life (39). These assessments were confirmed in a study where stigma related to diabetes was associated with elevated A1C; increased blood glucose variability; feelings of guilt, shame, blame, embarrassment, and isolation; and negative impacts on social life (32).…”
Section: Use Language That Is Free From Stigmamentioning
confidence: 99%
“…In a study of people living with diabetes (n 5 3,347), data from a self-administered questionnaire demonstrated that perceived stigma is associated with increased psychological distress, depressive symptoms, decreased social support, and decreased quality of life (39). These assessments were confirmed in a study where stigma related to diabetes was associated with elevated A1C; increased blood glucose variability; feelings of guilt, shame, blame, embarrassment, and isolation; and negative impacts on social life (32).…”
Section: Use Language That Is Free From Stigmamentioning
confidence: 99%
“…Difficulties in admission to schools or universities have forced many children to hide their diabetes. Therefore, the diabetes care team and other health care providers can play an important role in advocating for equal opportunities and where needed, special facilities (eg, access to a safe, clean place to test glucose and administer insulin, in school or workplace) for children with diabetes …”
Section: Barriers To Carementioning
confidence: 99%
“…Therefore, the diabetes care team and other health care providers can play an important role in advocating for equal opportunities and where needed, special facilities (eg, access to a safe, clean place to test glucose and administer insulin, in school or workplace) for children with diabetes. 93,94 Routine vaccinations should be provided for children with diabetes according to age-related recommendations. While specific recommendations vary by region, annual vaccination against influenza is also generally recommended for all individuals with diabetes above 6 months of age, 95 and pneumococcal and meningococcal vaccines are also recommended.…”
Section: Barriers To Carementioning
confidence: 99%
“…3,18,20,59 Studies have indicated that such consequences have an impact on the overall quality of life of individuals. 2,15,59 Furthermore, they undermine the public health response and cause a negative impact on their overall effectiveness. 18,19,21 The findings of this study have several implications for public health research and practice in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…5,14 People with different health conditions experience stigma that negatively affects their social, physical, psychological, and spiritual well-being. 2,12,15 It reduces the degree of access and uptake of health care services, causing the underdiagnosis of conditions, failing to detect mental health issues, and delaying and disrupting treatment. [16][17][18] Such consequences of stigma affect preventive and treatment measures for eliminating these diseases, ultimately hampering advancements in decreasing the burden of diseases.…”
Section: Introductionmentioning
confidence: 99%